Neurocognitive correlates of persisting concussion symptoms in youth. Issue 4 (2nd October 2022) - Anzalone, Christopher; Bridges, Rachel M.; Luedke, Jessica C.; Decker, Scott L.
Abstract: Many patients that experience a concussion have impairing symptoms that persist beyond typical recovery timeframes. Concussion symptoms often remit within a month, but persisting impairments are difficult to characterize and attribute to concussion given the poorly defined diagnostic criteria of post-concussion syndrome and inadequate understanding of the cognitive symptoms associated with this condition. The current study aims to clarify the cognitive profiles of school-aged concussion patients ( n = 21; N = 36; 64% male) that have persisting symptoms to improve the clinical identification methods for this condition. Logistic regression was used to explore the importance of cognitive processing speed and working memory for identifying patients with persisting concussion symptoms (PCS). Additional exploratory analyses were conducted to clarify cognitive domains that may be impacted by having PCS. Findings indicate processing speed and working memory abilities alone are not adequate to identify patients with PCS. Further, measures of processing speed, fluid reasoning, working memory, and long-term retrieval together were found to be necessary to identify those who had a prior concussion with PCS. These findings indicate clinical neuropsychological batteries must include measures of these four cognitive domains when assessing school-aged patients with chronic symptoms that extend beyond three months following injury.